Are patients with intracerebral haemorrhage disadvantaged in hospitals?. Issue 4 (21st November 2013) - Sheedy, Renee; Bernhardt, Julie; Levi, Christopher R.; Longworth, Mark; Churilov, Leonid; Kilkenny, Monique F.; Cadilhac, Dominique A.; ,
<x xml:space="preserve">Abstract</x> Background and Aims Providing evidence‐based clinical care reduces disability and mortality rates following stroke. We examined if compliance with evidence‐based processes of care were different for patients with intracerebral haemorrhage when compared with ischemic stroke and sought to describe differences in health outcomes during hospitalization and at time of discharge for these stroke subtypes. Methods The New South Wales acute stroke dataset was used. This included data from 50–100 consecutively admitted patients' medical records collected from 32 New South Wales hospitals between 2003 and 2010. Multivariable logistic regression analyses were conducted taking into account patient factors and clustering of patients by hospital. Results Ischemic stroke and intracerebral haemorrhage cases had similar demographic features (ischemic stroke n = 3467, mean age 74 years [standard deviation 13], 50% female; intracerebral haemorrhage n = 275, mean age 74 years [standard deviation 13], 48% female). Following multivariable analyses patients with intracerebral haemorrhage were less likely to be admitted to a stroke unit (adjusted odds ratio 0·65; 95% confidence interval 0·45–0·94) or receive an assessment from allied health (adjusted odds ratio 0·54; 95% confidence interval 0·33–0·89) than patients with ischemic stroke. Patients with intracerebral haemorrhage are also less likely to be independent (adjusted odds ratio 0·36; 95% confidence interval 0·3–0·5) at time of hospital discharge and had a greater odds of dying in hospital (adjusted odds ratio 2·1; 95% confidence interval 1·3–3·5). Patients that were admitted to a stroke unit had a greater odds of being independent (modified Rankin Score 0–2) at day 7–10 irrespective of stroke type or severity on admission (adjusted odds ratio 1·3; 95% confidence interval 1·01–1·66). Conclusions Following intracerebral haemorrhage, patients were less likely to be admitted to an acute stroke unit and receive allied health interventions. Admission to stroke units improved the likelihood of being independent at days 7–10 and, therefore, more should be done to encourage evidence‐based care for intracerebral haemorrhage.